(untitled) (Journal of the Bangladesh Agricultural University, 2010)
Effect of salinity on sprouting water uptake, ion uptake and metabolic efficiency of wheat seeds in the variety kanchan were studied in Jaydebpur. The treatments were 0, 4, 8, 12 and 16dS-m salinity level. The experiment was set in CRD with four replications. There were 50 seeds per petridish. Seeds were moistened with saline solution. Germination was recorded up to 72 hours with an interval of 12 hours. Water absorption rate was recorded up to 42 hours with an interval of 6 hours. Accumulation of Na+ and CI- ions were measured at 36 hours. Germination percentage decreased in high salinity level. Water uptake also decreased with an increase of salinity level but it was not so much drastic upto 8dS-m. Accumulation of Na+ and CI- increased when the seeds were treated with 4dS-m to 16dS-m saline solution. The result indicated that salinity induced delay and decrease in sprouting percentage through lower water uptake and higher accumulation of Na+ and CI- . Keywords: Salinity; Wheat; Water uptake; Seed metabolic efficiency; Ion uptake DOI: 10.3329/jbau.v8i1.6392 J. Bangladesh Agril. Univ. 8(1): 19-22, 2010